Chapter 1 Introduction - Mairs, Rachel (Taylor & Francis, 2021)
Within the basic historical framework, there is much that is controversial: the date of Bactrian independence, the order and relationships of Graeco-Bactrian and Indo-Greek kings, and the processes by which their rule came to an end. The most controversial question of all in Graeco-Bactrian and Indo-Greek studies has long been that of the cultural and ethnic affinities of these kingdoms and their inhabitants. This introduction presents an overview of the key concepts discussed in the subsequent chapters of this book. The book sets the Greek kingdoms of Central Asia within their wider geopolitical context. It surveys the intellectual history of studies of the Graeco-Bactrian and Indo-Greek kingdoms. The book provides an in-depth regional overview of the Hellenistic-period archaeology of Central Asia. It treats the written sources on the Greek kingdoms in Bactria and India.